The Influence of the Independence of the Board of Commissioners and the Size of the Board of Directors on Company Performance in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Rindiani, Antika; Azis, Azolla Degita; Rizqi, Muhammad Nur (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The purpose of study This is forknow influence from independence of the board of commissioners and size of the board of directors to performance company. Population in research This is company manufacture subsector food and beverages listed on the Indonesia Stock Exchange (BEI) in the period 2020-2023. Research methods use approach quantitative with technique taking sample use purposive sample and 8 companies were selected with 32 analysis data. Data analysis techniques using technique multiple linear regression with tool analysis used for processing the data is IBM SPSS (Statistical Package for the Social Sciences) version 27. Results of study This show that independence of the board of commissioners influential positive to performance companies, increasingly height of the board of commissioners independent so the more improve the retrieval process decision as well as more supervision effective. Size of the board of directors influential positive to performance company, the size of the board of directors is morebig can increase efficiency operational performance company with high number of board of directors.